Perancangan Dan Pembuatan Blood Cool Box Menggunakan Termoelectric Peltier Pada Beban Pendinginan 1 Liter - Fadilla Augusli Irwanda; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The process of blood distribution before transfusion requires a cooling unit that is able to maintain the temperature, so that blood can be maintained and not damaged before transfusion. Peltier elements are chosen to be used as coolants in the blood cool box because they are small so they can be operated in a limited space and operate at 12 volt. The design carried out in this case is the manufacture of blood cool boxes for the distribution of blood over long distances. The peltier element is used type of TEC1 12706. The ability of the cold side of the peltier element based on the calculation results of 18.65 Watt which is used for cooling the box. The lowest blood cool box temperature is obtained from no load testing of 14.23 ° C and the maximum load of 23.22 ° C. And the lower the temperature difference between the hot side and the cold side, the higher the amount of heat absorbed, and will affect the value of the Coefficient of Performance, which will be greater if the absorbed calorific value is greater.Keywords: Peltier Element, Blood Cool Box, Coefficient of Performance.